From Quality to Excellence with Supplier Partnerships (Journal of Universal Excellence, 2026)
Research Question (RQ): How does partnership with suppliers contribute to achieving organizational excellence in the supply chain?Purpose: The purpose of the research is to determine what strategies and practices are most effective in today's business environment which would ensure broader visions of development not only of the company, but also of suppliers.Method: We conducted a literature review in the Scopus database. The search process followed the guidelines of the PRISMA diagram, using inclusion criteria (English language, published scientific articles, full-text availability). Ten articles were included in the final analysis, which we processed using thematic analysis..Results: The research confirms that close cooperation, a high level of trust and commitment between suppliers and organizations are key factors for achieving sustainable company success. Such partnerships enable better coordination of processes, faster response to market changes and more efficient introduction of innovations, which strengthens the competitive advantage of both parties. In addition, the inclusion of green supply strategies further contributes to the sustainable success of organizations, as it promotes environmentally responsible operations, reduces negative impacts on the environment and increases the reputation and trust of stakeholders.Organization: The research has a positive impact on the organization, as a trustworthy partnership brings positive financial, environmental and social effects on all stakeholders in the long term.Society: The research has a positive impact on society, as the development of partnership relationships encourages cooperation and helps to achieve more environmentally sustainable supply chains.Originality: Organizations based on excellent partnership relationships contribute to the success of companies, to greater adaptability to market conditions and increase competitive advantage in a given environment. can be accelerated.Limitations/further research: While searching for relevant references in the databases, we found that the sociological aspect of partnership relationships is still little researched, but according to the findings of the research, the sociological aspect is key to increasing the success of two companies, so we suggest further research.
Keywords: partnership; suppliers; quality; sustainability; organization; excellence; supply chain; stakeholders; model EFQM 2020